Spatial Profiles of Phosphate in Roots Indicate Developmental Control of Uptake, Recycling, and Sequestration. Issue 4 (30th September 2020) - Sahu, Abira; Banerjee, Swayoma; Raju, Aditi Subramani; Chiou, Tzyy-Jen; Garcia, L. Rene; Versaw, Wayne K.
Abstract : Distinct spatiotemporal patterns for the uptake, recycling, and vacuolar sequestration of phosphate in the root indicate developmental control of cytosolic phosphate homeostasis. Abstract: The availability of inorganic phosphate (Pi) limits plant growth and crop productivity on much of the world's arable land. To better understand how plants cope with deficient and variable supplies of this essential nutrient, we used Pi imaging to spatially resolve and quantify cytosolic Pi concentrations and the respective contributions of Pi uptake, metabolic recycling, and vacuolar sequestration to cytosolic Pi homeostasis in Arabidopsis ( Arabidopsis thaliana ) roots. Microinjection coupled with confocal microscopy was used to calibrate a FRET-based Pi sensor to determine absolute, rather than relative, Pi concentrations in live plants. High-resolution mapping of cytosolic Pi concentrations in different cells, tissues, and developmental zones of the root revealed that cytosolic concentrations varied between developmental zones, with highest levels in the transition zone, whereas concentrations were equivalent in epidermis, cortex, and endodermis within each zone. Pi concentrations in all zones were reduced, at different rates, by Pi starvation, but the developmental pattern of Pi concentration persisted. Pi uptake, metabolic recycling, and vacuolar sequestration were distinguished in each zone by using cyanide to block Pi assimilation in wild-type plants and a vacuolar Pi transport mutant, and then measuring the subsequent change in cytosolic Pi concentration over time. Each of these processes exhibited distinct spatial profiles in the root, but only vacuolar Pi sequestration corresponded with steady-state cytosolic Pi concentrations. These results highlight the complexity of Pi dynamics in live plants and revealed developmental control of root Pi homeostasis, which has potential implications for plant sensing and signaling of Pi.